Telaah Kajian Nepotisme dalam Perspektif Islam - Sirait, Trian Azhari Fadilah; Sinaga, Ali Imran; Fajri, Fadlin (Instructional Development Journal, 2024)
Abstract: Nepotism is a moral and cultural problem that grows and develops in almost all institutions and bureaucracy, both economic and social, and its direction towards politics. The research objective is to present a study of nepotism in an Islamic perspective. This research method uses a type of library research. Library research is research conducted by collecting data and information through a study of various library materials. The results of the study, namely Nepotism occurs because of the relationship between the determinants of wisdom and authority contained in a person and a person's attitude, the use of authority that is unprofessional and disproportionate and power and the impact of nepotism, namely taking the rights of other people who have potential and presenting a sense of arrogance to have excessive power. tall.Abstrak: Nepotisme merupakan persoalan moral dan budaya yang tumbuh dan berkembang hampir seluruh institusi dan birokrasi, baik ekonomi, sosial dan arah arahnya ke politik. Tujuan Penelitian ialah untuk menyajikan telaah kajian nepotisme dalam perspektif islam. Metode Penelitian ini menggunakan jenis penelitian pustaka (library research). Penelitian pustaka merupakan penelitian yang dilakukan dengan mengumpulkan data dan informasi melalui kajian berbagai bahan pustaka. Hasil Penelitian yaitu Nepotisme terjadi karena adanya hubungan antar determinan kebijaksanaan dan wewenang yang terkandung dalam diri seseorang dan sikap seseorang penggunaan otoritas yang tidak profesional dan tidak proporsional dan kekuasaan serta dampak nepotisme yaitu mengambil hak orang lain yang memiliki potensi  dan menghadirkan rasa angkuh untuk memiliki kekuasaan yang tinggi.